Pembelajaran Kooperatif Tipe Berpikir Berpasangan Berbagi untuk Meningkatkan Aktivitas dan Hasil Belajar Matematika Siswa Kelas X Multimedia SMKN 1 Praya Tengah - Ahmad Sardan (Universitas Pendidikan Mandalika, 2022)
This study aims to improve the activities and learning outcomes of students of SMKN 1 Praya Tengah Class X Multimedia through cooperative learning, thinking in pairs and sharing. This research method uses classroom action research with 20 students as research subjects. The instruments of this research are observation sheets and tests. While the data analysis technique used quantitative descriptive analysis. The results showed an increase in student activity and learning outcomes, namely in the first cycle the average score of student learning activities was 10.3 with a fairly active category, while the average value of student learning outcomes was 66 and the percentage of completeness was 80%. In cycle II the average score of student learning activities is 14.22 with a very active category, while the average value of student learning outcomes is 75 and the percentage of completeness is 90%. So that the results of this study conclude that cooperative learning in thinking in pairs and sharing can increase the activity and learning outcomes of mathematics students at SMKN 1 Praya Tengah Class X Multimedia.